A New Topology of Modular Multilevel Converter With Voltage Self-Balancing Ability - Hongchun Shu; Shunguang Lei; Xincui Tian (IEEE Access, 2019)
The modular multilevel converter (MMC) has been used in the field of HVDC transmission due to its many advantages, but its voltage imbalance problem of sub-module capacitors affects the stable operation of the system. There are two kinds of methods for solving the capacitor voltage imbalance of the MMC sub-module. The one is voltage balancing algorithm and the other one is improved topology. However, the complexity of the voltage balancing algorithm increases sharply when the number of voltage levels is high, which is not suitable for the MMC system with a high number of voltage levels. In this paper, a new topology with bidirectional voltage self-balancing capability is proposed. This topology adds the voltage balancing circuit between sub-modules on the conventional MMC topology, realizing voltage self-balancing without voltage balancing algorithm, and having a better effect of inhibition phase-to-phase circulation. The bidirectional voltage balancing capability, the voltage balancing effect and the circulation inhibition effect of the bidirectional voltage self-balancing topology are verified by MATLAB/Simulink simulation and experiment.